Transient dynamic analysis: Performance evaluation of tactile measurement - Reschke, Gregor; Brosius, Alexander (Materials Research Proceedings)
Abstract. The assessment of mechanically joined connections, such as clinched connections, is usually conducted destructively. Applicable non-destructive testing methods like computed tomography are time-consuming and costly, or, like electrical resistance measurement, provide only a limited amount of information. A fast, non-destructive evaluation of the joints condition shall be made possible by using transient dynamic analysis (TDA). It is based on the introduction of sound waves and the evaluation of the response behavior after passing through the structure. This study focuses the application of TDA to clinched shear connections to evaluate the performance of the tactile measuring setup. Twenty-one series were investigated, covering variations in joining task, manufacturing and defect. The evaluation was carried out using machine learning to determine for which series characteristic signals may be detected. It was shown that a classification of the investigated specimens is possible, whereby the classification accuracy depends on the examined variation. Furthermore, the accuracy was evaluated as a function of frequency and results were concluded to identify the limits of the used measuring setup.
Keywords: Joining; Machine Learning; Transient Dynamic Analysis

In situ computed tomography – Analysis of settling effects during single-lap shear tests with clinch points - Köhler, D.; Troschitz, J; Kupfer, R.; Gude, M. (Materials Research Proceedings)
Abstract. In the field of mechanical engineering, destructive tests such as shear tests of mechanical joints are usually followed by imaging methods such as microsectioning or computed tomography (CT). They can help to interpret the measured load-displacement curves, analyze the failure behavior and validate numerical models. However, due to unloading, springback effects and crack closures can occur, which influence the state of the investigated specimen. In this context, in situ CT is able to explore the testing process with a specimen under load avoiding these influences. For in situ CT investigations, the displacement increase is interrupted at certain stop points. While the displacement is kept constant, the CT scan is performed. However, it was observed that the reaction force reduces during CT scanning, e. g. due to settling effects in the test setup. Although in situ CT is established now in research, little attention is paid to the uncertainties which arise from the discontinuous testing procedure. This study systematically explores the impact of these interruptions on the load-displacement behavior and the geometry of clinch points during tensile shear testing. To quantify the influence of the interruptions, loads at defined displacement levels and the final geometry are evaluated statistically. We found, that the load-displacement behavior of both test groups is similar. Despite some small but significant statistical deviations of the loads and the final geometry, our results show that, discontinuous testing has a high level of significance for the phenomena overserved in shear tests with clinch points.

In situ CT unter Temperatur: Thermokammer für thermoplastische FKV-Fügeprozesse - Dargel, Alrik; Köhler, Daniel; Gude, Maik; Kupfer, Robert (Tagungsband 43. Vortrags- und Diskussionstagung Werkstoffprüfung 2025)
Für das Verständnis und die Weiterentwicklung temperaturgestützter mechanischer Fü-geprozesse mit thermoplastischen Faser-Kunststoff-Verbunden (FKV) ist die zerstörungsfreie Analyse der Materialstruktur im Inneren des Fügepunktes während der Entstehung und Belastung erforderlich. Die Kombination aus Prüfung unter Temperatureinfluss und in situ Computertomographie (CT) eröffnet neue Möglichkeiten für die Fügeprozessanalyse. Dazu wurde dazu eine Thermokammer entwickelt und in eine bestehende in situ CT-Anlage integriert. Anwendungsszenarien sind die Herstellung und Prüfung von Fügepunkten unter Temperatur. Die Erwärmung erfolgt über einzeln regelbare Heizzonen, welche eine gezielte Temperaturführung über die gesamte Probengeometrie ermöglichen. Die Temperaturkurve eines Aufheizversuchs, sowie eine Röntgenprojektion einer Probe innerhalb der Thermokammer validie-ren die Konstruktion.
Keywords: in situ CT; Thermokammer; Thermoplastische FKV

In Situ CT of Clinch Points – Enhancing Interface Detectability Using Electroplated Patterns of Radiopaque Materials - Köhler, Daniel; Dargel, Alrik; Troschitz, Juliane; Gude, Maik; Kupfer, Robert (Journal of Nondestructive Evaluation)
Abstract A clinch point’s quality is usually assessed using ex situ destructive testing methods. These, however, are unable to detect phenomena immediately during the joining process. For instance, elastic deformations reverse and cracks close after unloading. In situ methods such as the force-displacement evaluation are used to investigate a clinching process, though deviations in the clinch point geometry cannot be derived with this method. To overcome these limitations, the clinching process can be investigated using in situ computed tomography (in situ CT). When investigating the clinching of aluminum parts in in situ CT, the sheet-sheet interface is hardly visible. Earlier investigations showed that radiopaque materials can be applied between the joining parts to enhance the detectability of the sheet-sheet interface. However, the layers cause strong artefacts, break during the clinching process or change the clinch joint’s properties significantly. In this paper, a minimally invasive method to enhance the interface detectability is presented. First, the aluminum oxide layer is removed by etching. Second, the specimen is electroplated with copper or gold, respectively. In some cases, a mask is applied to create a cross-shaped plating pattern. Then, the plated specimen is clinched with a non-plated counterpart and the interface detectability of the clinch points is assessed in CT scans. It is shown that a copper plating of 2.6–4 μm can visualize some parts of the interface, while 7–9 μm is suitable to enhance the detectability of the sheet-sheet interface almost continuously.

Quality assurance of clinched joints using explainable machine learning - Gerritzen, Johannes; Chopra, Kunal; Reschke, Gregor; Hornig, Andreas; Brosius, Alexander; Gude, Maik (Journal of Advanced Joining Processes)

Local Deformation and Failure of Composites during Self-Piercing Riveting: A CT-Based Microstructure Investigation - Dargel, Alrik; Gröger, Benjamin; Schlichter, Malte Christian; Gerritzen, Johannes; Köhler, Daniel; Meschut, Gerson; Gude, Maik; Kupfer, Robert (Proceedings of the 8th International Conference on Integrity-Reliability-Failure (IRF2025))
The use of continuous fiber-reinforced thermoplastics (FRTP) in automotive industry increases due to their excellent material properties and possibility of rapid processing. The scale spanning heterogeneity of their material structure and its influence on the material behavior, however, presents significant challenges for most joining technologies, such as self-piercing riveting (SPR). During mechanical joining, the material structure is significantly altered within and around the joining zone, heavily influencing the material behavior. A comprehensive understanding of the underlying phenomena of material alteration during the SPR process is essential as basis for validating numerical simulations. This study examines the material structure at ten stages of a step-setting test of SPR with two FRTP sheets with glass-fiber reinforcement. Utilizing X-ray computed tomography (CT), the damage phenomena within different areas of the setting test are analyzed three-dimensionally and key parameters are quantified. Dominating phenomena during the penetration of the rivet into the laminate are fiber failure (FF), interfiber failure (IFF) and fiber bending, while delamination, fiber kinking and roving splitting are also observed. At the final stages, the bottom layers of the second sheet collapse and form a bulge into the cavity of the die.
Keywords: self-piercing riveting; computed tomography; thermoplastic composites; process-structure-interaction

In-situ computed tomography and transient dynamic analysis – failure analysis of a single-lap tensile-shear test with clinch points - Reschke, Gregor; Köhler, Daniel; Kupfer, Robert; Troschitz, Juliane; Gude, Maik; Brosius, Alexander (Proceedings of the Institution of Mechanical Engineers, Part E: Journal of Process Mechanical Engineering)
Clinching is a mechanical joining technology, in which a mainly form-fit joint is created by means of local cold forming. To characterize the load-bearing behavior of such joints, they are typically analyzed destructively, for example by tensile-shear tests in combination with metallographic sections. However, both the initiation and progress of failure can only be described to a limited extent by this method. Furthermore, these tests allow only limited conclusions about clinch points under in-service loading. More purposefully, clinch points can be analyzed nondestructively by combining in-situ computed tomography (CT) and transient dynamic analysis (TDA). The TDA continuously measures the dynamic behavior of the specimen and indicates failure events like crack initiation, which then can be evaluated thoroughly by stopping the test and performing a CT scan. To qualify the TDA for this task, it is necessary to link the observed damage behavior with specific dynamic characteristics. In this work, the complementation of in-situ CT and TDA is investigated by testing a clinched single-lap tensile-shear specimen made of aluminum. The testing procedure is stepwise: at certain displacement levels, the specimen is investigated by in-situ CT and TDA. While the in-situ CT provides the location, extent, and development of the failure phenomena, the TDA uses this information to evaluate the dynamic signal and detect relevant frequency ranges, which indicate damage events. The results demonstrate, that failure initiation and progression can be analyzed efficiently by combining both measuring systems. The TDA reliably detects relevant signal changes in the monitored frequency band. By means of in-situ computed tomography, the corresponding failure phenomena can be described in detail, enhancing the understanding of the load-bearing and deformation behavior of clinch points. The concatenation of characteristic signal changes and observed failure phenomena can henceforth be transferred to analyze complex structures during operation nondestructively by TDA.
Keywords: Clinching; Non-destructive testing; Transient Dynamic Analysis

In-situ computed tomography and transient dynamic analysis – failure analysis of a single-lap tensile-shear test with clinch points - Reschke, G; Köhler, D; Kupfer, R; Troschitz, J; Gude, M; Brosius, A (Proceedings of the Institution of Mechanical Engineers, Part E: Journal of Process Mechanical Engineering)
Clinching is a mechanical joining technology, in which a mainly form-fit joint is created by means of local cold forming. To characterize the load-bearing behavior of such joints, they are typically analyzed destructively, for example by tensile-shear tests in combination with metallographic sections. However, both the initiation and progress of failure can only be described to a limited extent by this method. Furthermore, these tests allow only limited conclusions about clinch points under in-service loading. More purposefully, clinch points can be analyzed nondestructively by combining in-situ computed tomography (CT) and transient dynamic analysis (TDA). The TDA continuously measures the dynamic behavior of the specimen and indicates failure events like crack initiation, which then can be evaluated thoroughly by stopping the test and performing a CT scan. To qualify the TDA for this task, it is necessary to link the observed damage behavior with specific dynamic characteristics. In this work, the complementation of in-situ CT and TDA is investigated by testing a clinched single-lap tensile-shear specimen made of aluminum. The testing procedure is stepwise: at certain displacement levels, the specimen is investigated by in-situ CT and TDA. While the in-situ CT provides the location, extent, and development of the failure phenomena, the TDA uses this information to evaluate the dynamic signal and detect relevant frequency ranges, which indicate damage events. The results demonstrate, that failure initiation and progression can be analyzed efficiently by combining both measuring systems. The TDA reliably detects relevant signal changes in the monitored frequency band. By means of in-situ computed tomography, the corresponding failure phenomena can be described in detail, enhancing the understanding of the load-bearing and deformation behavior of clinch points. The concatenation of characteristic signal changes and observed failure phenomena can henceforth be transferred to analyze complex structures during operation nondestructively by TDA.

In-situ computed tomography analysis of the failure mechanisms of thermomechanically manufactured joints with auxiliary joining element - Borgert, T; Köhler, D; Wiens, E.; Kupfer, R; Troschitz, J; Homberg, W; Gude, M (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
Lightweight design by using low-density and load-adapted materials can reduce the weight of vehicles and the emissions generated during operation. However, the usage of different materials requires innovative joining technologies with increased versatility. In this investigation, the focus is on describing and characterising the failure behaviour of connections manufactured by an innovative thermomechanical joining process with adaptable auxiliary joining elements in single-lap tensile-shear tests. In order to analyse the failure development in detail, the specimens are investigated using in-situ computed tomography (in-situ CT). Here, the tensile-shear test is interrupted at points of interest and CT scans are conducted under load. In addition, the interrupted in-situ testing procedure is validated by comparing the loading behaviour with conventional continuous tensile-shear tests. The results of the in-situ investigations of joints with varying material combinations clearly describe the cause of failure, allowing conclusions towards an improved joint design.

In-situ CT of the clinching process – Influence of settling effects due to process interruptions - Köhler, D.; Kupfer, R.; Troschitz, J.; Gude, M. (Materials Research Proceedings)
Abstract. In lightweight constructions, clinching represents a cost-effective solution, in which joints are produced by local cold forming of the joining parts. Clinching phenomena are typically evaluated using destructive testing methods. While these methods influence the clinch point’s state, in-situ computed tomography (in-situ CT) is able to explore the clinching process with a specimen under load. Here, the path-controlled clinching process is interrupted at certain displacement levels and the specimen is scanned by CT while remaining in a stationary state. These interruptions are always accompanied by settling effects reducing the reaction force. Therefore, in this work, the influence of these interruptions on the force-displacement behavior during clinching and on the final clinch point’s geometric properties is investigated.

Transiente Dynamische Analyse – Vergleich zeit- und frequenzdiskreter Auswertemethoden anhand geclinchter Aluminiumverbindungen - Reschke, Gregor; Brosius, Alexander (Werkstoffe und Bauteile auf dem Prüfstand)

Anrisserkennung an geclinchten Proben während einer zyklischen Belastung unter Nutzung eines Scanning Laser Doppler Vibrometers - Brosius, Alexander; Ewenz, Lars; Stephan, Richard; Zimmermann, Martina (Tagung Werkstoffprüfung 2022)

Investigations on Continuous Transient Dynamic Analysis of Clinched Aluminum Sheets - Reschke, Gregor; Brosius, Alexander (Lecture Notes in Production Engineering)

Comparison of ex- and in-situ investigations of clinched single-lap shear specimens - Köhler, Daniel; Kupfer, Robert; Troschitz, Juliane; Gude, Maik (Materials Research Proceedings)
Abstract. Force-displacement measurements and macrosections are commonly used methods to validate numerical models of clinching processes. However, these ex-situ methods often lead to springback of elastic deformations and crack-closing after unloading. In contrast, the in-situ computed tomography (CT) can provide three-dimensional images of the clinching point under loading conditions. So far, the quantity of elastic springback that causes measuring deviations between in- and ex-situ measurements is not determined. In this paper, a method is described to quantitatively compare the results of in-situ CT, ex-situ CT and CT scans of cut specimens, which are prepared for macrosectioning, among each other. The method is applied to a single-lap shear test of two clinched aluminum sheets. Here, the test is conducted to specific process steps, then the specimen is CT scanned in-situ (during loading) and ex-situ (after unloading). Subsequently, the specimens are cut for macrosectioning and CT scanned. Finally, the outer contours and the interfaces of cross section images are determined by digital image analysis and the deviations over the clinching point between ex- and in-situ methods are calculated.

In-situ Computed Tomography and Transient Dynamic Analysis of a Single-Lap Shear Test with a Composite-Metal Clinch Point - Köhler, Daniel; Stephan, Richard; Kupfer, Robert; Troschitz, Juliane; Brosius, Alexander; Gude, Maik (Lecture Notes in Production Engineering)

Clinching in In Situ CT—A Novel Validation Method for Mechanical Joining Processes - Köhler, Daniel; Kupfer, Robert; Troschitz, Juliane; Gude, Maik (The Minerals, Metals & Materials Series)
Force–displacement measurements and micrograph analyses are commonly used methods to validate numerical models of clinching processes. However, these methods often lead to resetting of elastic deformations and crack- closing after unloading. In contrast, the in situ computed tomography (CT) can provide three-dimensional images of the clinch point under loading conditions. In this paper, the potential of the in situ investigation of a clinching process as validation method is analyzed. For the in situ testing, a tailored test set-up featuring a beryllium cylinder for load-bearing and clinching tools made from ultra-high-strength titanium and Si3N4 are used. In the experiments, the clinching of two aluminum sheets is interrupted at specific process steps in order to perform the CT scans. It is shown that in situ CT visualizes the inner geometry of the joint at high precision and that this method is suitable to validate numerical models.
Keywords: Clinching; Non-destructive testing; Computed tomography; In situ CT

Joining Processes for Fibre-Reinforced Thermoplastics: Phenomena and Characterisation - Troschitz, Juliane; Gröger, Benjamin; Würfel, Veit; Kupfer, Robert; Gude, Maik (Materials)
Thermoplastic composites (TPCs) are predestined for use in lightweight structures, especially for high-volume applications. In many cases, joining is a key factor for the successful application of TPCs in multi-material systems. Many joining processes for this material group are based on warm forming the joining zone. This results in a change of the local material structure characterised by modified fibre paths, as well as varying fibre contents, which significantly influences the load-bearing behaviour. During the forming process, many different phenomena occur simultaneously at different scales. In this paper, the deformation modes and flow mechanisms of TPCs during forming described in the literature are first analysed. Based on this, three different joining processes are investigated: embedding of inserts, moulding of contour joints, and hotclinching. In order to identify the phenomena occurring in each process and to describe the characteristic resulting material structure in the joining zones, micrographs as well as computed tomography (CT) analyses are performed for both individual process stages and final joining zones.

Characterisation of lateral offsets in clinch points with computed tomography and transient dynamic analysis - Köhler, D.; Sadeghian, B.; Troschitz, J.; Kupfer, R.; Gude, M.; Brosius, A. (Journal of Advanced Joining Processes)
Clinching is a very cost-efficient method for joining two or more sheets made of identical or different materials. However, the current evaluation methods cannot confirm the critical geometrical features of joints such as neck thickness, undercut, and bottom thickness. Furthermore, the effects caused by joining process such as elastic deformation and crack-closure are significant for the joining quality, but often earn insufficient attention. Therefore, computed tomography (CT) and Transient Dynamic Analysis (TDA) as an ultrasonic testing and evaluation procedure are combined to overcome the obstacles mentioned above. In order to have a well-defined and reproducible typical geometrical error in clinching, specimens with a pre-specified lateral offset of the punch with 0.1 mm, 0.2 mm are as well as with no lateral offset are investigated using CT. The specimens are treated with conductive copper varnish in varying intensities to support the two sheets' distinguishability in the CT measurement. The subsequently extracted surfaces from CT-scan data are used to create three-dimensional models for a numerical Transient Dynamic Analysis. Hereby, a harmonic force is applied to one sheet and the transferred energy is determined at the opposite side of the clinch point on the other sheet. The transmitted energy can be used as a quantitative measure for the joining quality. This setup is simulated by means of Finite-Element-Method and the specimens are investigated experimentally using a piezo actuator and a piezo sensor. The novelty of the results presented here is the completely non-destructive investigation of joint specimen by CT of similar materials with a contrast given foil in between the sheets and the subsequent TDA, which can easily detect difference between the specimens by evaluation of the energy dissipation of the joints.

Investigations on Combined in situ CT and Acoustic Analysis during Clinching - Köhler, Daniel; Stephan, Richard; Kupfer, Robert; Troschitz, Juliane; Brosius, Alexander; Gude, Maik (Key Engineering Materials)
Clinching is a cost efficient method for joining components in series production. To assure the clinch point’s quality, the force displacement curve during clinching or the bottom thickness are monitored. The most significant geometrical characteristics of the clinch point, neck thickness and undercut, are usually tested destructively by microsectioning. However, micrograph preparation goes ahead with a resetting of elastic deformations and crack-closing after unloading. To generate a comprehensive knowledge of the clinch point’s inner geometry under load, in-situ computed tomography (CT) and acoustic testing (TDA) can be combined. While the TDA is highly sensitive to the inner state of the clinch point, it could detect critical events like crack development during loading. If such events are indicated, the loading process is stopped and a stepped in-situ CT of the following crack and deformation development is performed. In this paper, the concept is applied to the process of clinching itself, providing a detailed three-dimensional insight in the development of the joining zone. A test set-up is used which allows a stepwise clinching of two aluminium sheets EN AW 6014. Furthermore, this set-up is positioned within a CT system. In order to minimize X-ray absorption, a beryllium cylinder is used within the set-up frame and clinching tools are made from Si3N4. The actuator and sensor necessary for the TDA are integrated in the set-up. In regular process steps, the clinching process is interrupted in order to perform a TDA and a CT scan. In order to enhance the visibility of the interface, a thin tin layer is positioned between the sheets prior clinching. It is shown, that the test-set up allows a monitoring of the dynamic behaviour of the specimen during clinching while the CT scans visualize the inner geometry and material flow non-destructively.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Experimental Measurement Method and Evaluation of an Analytical Approach for Sound Conduction through Multiple Clinched Sheets - Stephan, Richard; Brosius, Alexander (The 28th Saxon Conference on Forming Technology SFU and the 7th International Conference on Accuracy in Forming Technology ICAFT)
The conduction of structure-borne sound through joints causes energy dissipation. The sound reduction index describes this energy loss as a level decrease in the particle velocity across series-connected damping elements for which the superposition principle applies. This simple model can help to develop a testing method for joints based on this characteristic energy loss. In this paper, this model is experimentally evaluated for multiple in-series clinched aluminium sheets. Samples connected by several clinch points arranged in parallel are investigated experimentally, and the results are discussed.
Keywords: clinching; mechanical joining; damping; model; evaluation; dynamics